A Validated Method for the Quality Control of Andrographis paniculata Preparations - Karioti, Anastasia; Timoteo, Patricia; Bergonzi, Maria Camilla; Bilia, Anna Rita (Planta Medica, 2017)
Andrographis paniculata is a herbal drug of Asian traditional medicine largely employed for the treatment of several diseases. Recently, it has been introduced in Europe for the prophylactic and symptomatic treatment of common cold and as an ingredient of dietary supplements. The active principles are diterpenes with andrographolide as the main representative. In the present study, an analytical protocol was developed for the determination of the main constituents in the herb and preparations of A. paniculata. Three different extraction protocols (methanol extraction using a modified Soxhlet procedure, maceration under ultrasonication, and decoction) were tested. Ultrasonication achieved the highest content of analytes. HPLC conditions were optimized in terms of solvent mixtures, time course, and temperature. A reversed phase C18 column eluted with a gradient system consisting of acetonitrile and acidified water and including an isocratic step at 30 °C was used. The HPLC method was validated for linearity, limits of quantitation and detection, repeatability, precision, and accuracy. The overall method was validated for precision and accuracy over at least three different concentration levels. Relative standard deviation was less than 1.13%, whereas recovery was between 95.50% and 97.19%. The method also proved to be suitable for the determination of a large number of commercial samples and was proposed to the European Pharmacopoeia for the quality control of Andrographidis herba.
Keywords: Andrographis paniculata; Acanthaceae; quality control; diterpenes; andrographolide; HPLC-DAD-ESI-MS